The Anti-Bottleneck Principle in Employment Discrimination Law - Joseph Fishkin (Washington University Law Review, 2014)
State legislatures and the Equal Opportunity Employment Commission (EEOC) have moved in parallel in recent years to provide new protections for the employment prospects of some surprising groups: people who are unemployed, people who have poor credit, and people with past criminal convictions. These new protections confound our usual theories of what antidiscrimination law is about. These groups are disanalogous in a variety of respects to groups defined by such characteristics as race, sex, and national origin. But the legislators and regulators enacting these new protections were responding to pervasive problems they observed in the opportunity structure of our society—problems of a particular kind that I call bottlenecks. Essentially, these legal actors judged that poor credit, unemployment, and past criminal convictions were having too outsized an effect on a person’s employment prospects. If many or most employers demand good credit, then good credit becomes a serious bottleneck: a narrow place through which workers must pass to reach a wide range of opportunities on the other side. This Article argues that the anti-bottleneck principle—the principle that the law ought to ameliorate severe bottlenecks in the opportunity structure where it can feasibly do so—is not only a way of understanding these new, cutting-edge protections, but also a way of understanding much of the project of Title VII and our existing body of antidiscrimination law. This Article explores the role the anti-bottleneck principle plays in legislators’ decisions to enact antidiscrimination laws and in decisions by judges and by the EEOC about how to interpret and enforce such laws. The Article argues that the anti-bottleneck idea is at the heart of both disparate treatment law and disparate impact law—and that it should cause us to think differently about the function of disparate impact law. The EEOC lawyers who started down the path that led to Griggs v. Duke Power understood that general ability tests were becoming a major bottleneck in the opportunity structure. By limiting the use of those tests, Griggs ameliorated a bottleneck that had arbitrarily constrained the opportunities of many whites as well as blacks. Finally, turning from the positive to the normative, this Article defends the central—if previously unacknowledged—role that the anti-bottleneck principle plays in our law of equal employment opportunity. It is a profound challenge for any legal system to promote “equal opportunity” in a world of pervasive difference and inequality, where the mechanisms that perpetuate inequality shift over time. The anti-bottleneck principle turns out to be a strong and surprisingly practical response to these challenges.
Keywords: Equal Opportunity Employment Commission; EEOC; anti-bottleneck; bottlenecks